2008
DOI: 10.1002/hed.20854
|View full text |Cite
|
Sign up to set email alerts
|

Retroesophageal subclavian artery—Esophageal fistula: A rare complication of a salivary bypass tube

Abstract: Salivary bypass tubes have been used with great success in preventing neck wound contamination from saliva and decreasing the risk of pharyngoesophageal stenosis. However, complications from esophageal tubes and risk factors for these complications should not be overlooked. Complications can be fatal, as demonstrated in this case of esophageal-subclavian artery fistulization. Retroesophageal subclavian artery (RRESA) is 1 of the most common anatomical variations of the aortic system. Typically producing no sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…The presence of an aberrant right subclavian artery (ARSA) is the most common aortic arch anomaly, present in 0.2–2.5% of the population [ 4 , 5 ]. The discovery of this variation is usually an incidental finding on imaging studies performed for other reasons, but the anomaly is more prevalent in patients with Down's syndrome and patients with chromosome 22q11 deletions [ 5 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of an aberrant right subclavian artery (ARSA) is the most common aortic arch anomaly, present in 0.2–2.5% of the population [ 4 , 5 ]. The discovery of this variation is usually an incidental finding on imaging studies performed for other reasons, but the anomaly is more prevalent in patients with Down's syndrome and patients with chromosome 22q11 deletions [ 5 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Serious complications from pharyngeal SBT are rare but have been described as a direct result of their use. One patient developed peritonitis and went on to die following migration of the tube into the ileum [47] and arterio-esophageal fistulas have been described, one of which was fatal [48, 49]. However, they are generally safe with only mild complications such as discomfort and granulation tissue formation [43].…”
Section: Discussionmentioning
confidence: 99%
“…6,7 A lethal MSBT-associated fistula from a retroesophageal subclavian artery has also been described. 8 In a review of patients who underwent fasciocutaneous reconstruction of circumferential pharyngoesophageal defects using an anterolateral thigh flap wrapped around an MSBT that was sutured to the tongue base, Murray et al 2 reported MSBT migration into the stomach in 2 of 14 patients. Based on these findings, the authors subsequently sutured the MSBT to a nasogastric tube, which was sutured to the nasal septum.…”
Section: Discussionmentioning
confidence: 99%